A new framework for the design and evaluation of a learning institution's student engagement activities. Issue 11 (2nd November 2019) - Wilson, Caroline; Broughan, Christine; Marselle, Melissa
ABSTRACT: In this article we explore the potential for attempts to encourage student engagement to be conceptualised as behaviour change activity, and specifically whether a new framework to guide such activity has potential value for the Higher Education (HE) sector. The Behaviour Change Wheel (BCW) (Michie, Susan, Maartje M van Stralen, and Robert West. 2011. "The Behaviour Change Wheel: A New Method for Characterising and Designing Behaviour Change Interventions." Implementation Science : IS 6 (1): 42. doi:10.1186/1748-5908-6-42 ) is a framework for the systematic design and development of behaviour change interventions. It has yet to be applied to the domain of student engagement. This article explores its potential, by assessing whether the BCW comprehensively aligns with the state of student engagement as currently presented in the HE literature. This work achieves two things. It firstly allows a prima facie assessment of whether student engagement activity can be readily aligned with the BCW framework. It also highlights omissions and prevalence of activity types in the HE sector, compared with other sectors where behaviour change practice is being successfully applied.